890 new foundation and diploma students register for session 2024 2025 at UMPSA - Siti Nur Azwin, Ibrahim (UMPSA, 2024)
GAMBANG, 27 July 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) welcomed a total of 890 new students for the foundation and diploma programmes for the 2024/2025 academic session.